Integrated modeling of labile and glycated hemoglobin with glucose for enhanced diabetes detection and short-term monitoring - José Antonio Romero-Rosales; David G. Aragones; José Escribano-Serrano; Marisa González Borrachero; Alfredo Michán Doña; Francisco J. Macías López; María Angeles Santos Mata; Inmaculada Naranjo Jiménez; María Jesús Casamitjana Zamora; Hélia Serrano; Juan Belmonte-Beitia; María Rosa Durán; et al. (iScience, 2024)
Summary: Metabolic biomarkers, particularly glycated hemoglobin and fasting plasma glucose, are pivotal in the diagnosis and control of diabetes mellitus. Despite their importance, they exhibit limitations in assessing short-term glucose variations. In this study, we propose labile hemoglobin as an additional biomarker, providing insightful perspectives into these fluctuations. By utilizing datasets from 40,652 retrospective general participants and conducting glucose tolerance tests on 60 prospective pediatric subjects, we explored the relationship between plasma glucose and labile hemoglobin. A mathematical model was developed to encapsulate short-term glucose kinetics in the pediatric group. Applying dimensionality reduction techniques, we successfully identified participant subclusters, facilitating the differentiation between diabetic and non-diabetic individuals. Intriguingly, by integrating labile hemoglobin measurements with plasma glucose values, we were able to predict the likelihood of diabetes in pediatric subjects, underscoring the potential of labile hemoglobin as a significant glycemic biomarker for diabetes research.